2010
DOI: 10.1007/82_2009_2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Varicella Zoster Virus in Latently Infected Human Ganglia: Physical State and Abundance of VZV DNA, Quantitation of Viral Transcripts and Detection of VZV-Specific Proteins

Abstract: Varicella zoster virus (VZV) establishes latency in neurons of human peripheral ganglia where the virus genome is most likely maintained as a circular episome bound to histones. There is considerable variability among individuals in the number of latent VZV DNA copies. The VZV DNA burden does not appear to exceed that of herpes simplex type 1 (HSV-1). Expression of VZV genes during latency is highly restricted and is regulated epigenetically. Of the VZV open reading frames (ORFs) that have been analyzed for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…In contrast, VZV gene expression during productive replication in a fully permissive cell type follows an ordered cascade, with the expression of immediate-early, early, and late genes in a sequential manner (28,35). VZV glycoproteins (late gene products) are not expressed during latent VZV infection (6), and thus, their detection in neurons provides a useful means to exclude true latency. We therefore examined ganglionic sections from cases following herpes zoster for VZV gE by IHC staining.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, VZV gene expression during productive replication in a fully permissive cell type follows an ordered cascade, with the expression of immediate-early, early, and late genes in a sequential manner (28,35). VZV glycoproteins (late gene products) are not expressed during latent VZV infection (6), and thus, their detection in neurons provides a useful means to exclude true latency. We therefore examined ganglionic sections from cases following herpes zoster for VZV gE by IHC staining.…”
Section: Resultsmentioning
confidence: 99%
“…Both VZV 63 and VZV gE proteins were found exclusively in neurons, but not in nonneuronal cells. Importantly, transcripts corresponding to VZV ORFs 21, 29, 62, 63, and 68 (gE) are present in latently infected human ganglia (1,19). VZV gE is also present in vivo months after experimental infection of human dorsal root ganglia (22).…”
Section: Discussionmentioning
confidence: 99%
“…Human cadaveric ganglia have been used to study viral transcripts and proteins expressed during latency. Although several VZV mRNAs and proteins have been detected in human ganglia (12), more recent studies suggest that viral protein expression during latency observed in certain prior studies may be due to nonspecific Ab staining (13,14), and viral mRNA expression has been postulated to reflect postmortem events rather than the true latent state (15). Recent advances in stem cell research allow a virtually unlimited supply of human neurons differentiated from hESCs or human-induced pluripotent stem cells that have not been infected with VZV.…”
mentioning
confidence: 99%